2023
DOI: 10.1192/bjp.2023.79
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a 4-week course of repeated subcutaneous ketamine injections for treatment-resistant depression (KADS study): randomised double-blind active-controlled trial

Abstract: Background Prior trials suggest that intravenous racemic ketamine is a highly effective for treatment-resistant depression (TRD), but phase 3 trials of racemic ketamine are needed. Aims To assess the acute efficacy and safety of a 4-week course of subcutaneous racemic ketamine in participants with TRD. Trial registration: ACTRN12616001096448 at www.anzctr.org.au. Method This phase 3, double-blind, randomised, active-controlled multicentre trial was conducted at seven mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Loo (Loo et al, 2016), who compared IV, IM and subcutaneous dosing routes for doses of 0.1 to 0.5 mg/kg, reported dose-responses for all routes of administration. More recently, the same research group (Loo et al, 2023) reported that ketamine dosed flexibly (0.5-0.9 mg/kg) had greater effects on depression ratings than ketamine at a fixed dose of 0.5 mg/kg. Chilukuri reported that mood responses to ketamine doses of 0.25 mg/kg and 0.5 mg/kg in patients with MDD were equivalent (Chilukuri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Loo (Loo et al, 2016), who compared IV, IM and subcutaneous dosing routes for doses of 0.1 to 0.5 mg/kg, reported dose-responses for all routes of administration. More recently, the same research group (Loo et al, 2023) reported that ketamine dosed flexibly (0.5-0.9 mg/kg) had greater effects on depression ratings than ketamine at a fixed dose of 0.5 mg/kg. Chilukuri reported that mood responses to ketamine doses of 0.25 mg/kg and 0.5 mg/kg in patients with MDD were equivalent (Chilukuri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that most patients had comorbid MDD and that subcutaneous administration was the preferred route in the given sample. This route is less complex, and evidence suggests a similar efficacy but better tolerability when compared with the intravenous route 30,31 . The absence of life-threatening or other serious adverse effects, such as psychosis or mania, contribute to the debate as to whether OCD should remain an exclusion criterion in trials involving esketamine.…”
Section: Discussionmentioning
confidence: 99%
“…This route is less complex, and evidence suggests a similar efficacy but better tolerability when compared with the intravenous route. 30,31 The absence of life-threatening or other serious adverse effects, such as psychosis or mania, contribute to the debate as to whether OCD should remain an exclusion criterion in trials involving esketamine. Furthermore, dissociative symptoms, frequently associated with esketamine and ketamine, were not documented as serious adverse events, with transient and mild psychotomimetic effects in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…[97][98][99][100][101][102] A phase III trial in 174 participants indicated that when dosing is incremented based on the participant's response rather than fixed, ketamine is associated with a significantly higher remission rate (19.6%) than the anesthetic benzodiazepine midazolam (2.0%) in patients with treatment-resistant depression. 103 Modes of administration other than IV infusion, such as IM, subcutaneous, oral, and intranasal (IN) routes, have also found success, [104][105][106][107][108] and in 2019, IN esketamine was approved by the US FDA under the name Spravato. The effects of a single dose of ketamine emerge within hours of administration (weighted effect size averages of depression scores (N 5 518) following a single 0.5 mg/kg infusion of ketamine within 24 hours: d 5 1.012; at 24 hours: d 5 0.96) and can last up to approximately 2 weeks.…”
Section: Ketamine and Depressionmentioning
confidence: 99%